DESTRUCTION OF MAJOR CARP FINGERLINGS IN A SECTION OF RIVER GANGA AND ITS PROBABLE ADVERSE EFFECTS ON FISH PRODUCTION - Jhingran, V G; Chakraborty, R D (Indian Journal of Fisheries, 2016)
Almost every year, towards the beginning of autumn when the floodscommence to subside, the fingerlings of major carps form a sizeable riverinefishery in North India. This fishery is generally of a brief duration andoften lasts for as short a time-span as 10 to 14 days, but it is extensive andis practised so intensely that for a few days the riverine catches consistalmost exclusively of carp fingerlings. The types of areas fished comprisesmall creeks, rivulets, and fields inundated during the rains. The recedingflood waters in autumn, in such habitats, leave the fingerUngs of carps strandedin shallows, rendering them an easy prey to fishermen, who capture themin great quantities.